Primary Failure of the Arteriovenous Fistula in Patients with Chronic Kidney Disease Stage 4/5 - Gjorgjievski, Nikola; Dzekova Vidimliski, Pavlina; Gerasimovska, Vesna; Pavleska-Kuzmanovska, Svetlana; Gjorgievska, Julija; Dejanov, Petar; Sikole, Aleksandar; Ivanovski, Ninoslav (Scientific Foundation SPIROSKI, 2019)
An Arteriovenous fistula (AVF) is a creation of the natural blood vessels. It is a "gate of life" for the patients on hemodialysis.